2017
DOI: 10.1007/s10571-017-0463-7
|View full text |Cite
|
Sign up to set email alerts
|

Explosive Blast Loading on Human 3D Aggregate Minibrains

Abstract: The effects of primary explosive blast on brain tissue still remain mostly unknown. There are few in vitro models that use real explosives to probe the mechanisms of injury at the cellular level. In this work, 3D aggregates of human brain cells or brain microphysiological system were exposed to military explosives at two different pressures (50 and 100 psi). Results indicate that membrane damage and oxidative stress increased with blast pressure, but cell death remained minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…3D LUHMES and BrainSpheres were produced by constant gyratory shaking as previously described [54, 56, 58–60]. Both LUHMES and BrainSpheres are highly reproducible in size (200–250 μm for LUHMES and 300–350 μm for BrainSpheres) and cellular composition from batch to batch and experiment to experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D LUHMES and BrainSpheres were produced by constant gyratory shaking as previously described [54, 56, 58–60]. Both LUHMES and BrainSpheres are highly reproducible in size (200–250 μm for LUHMES and 300–350 μm for BrainSpheres) and cellular composition from batch to batch and experiment to experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Both LUHMES and BrainSpheres are highly reproducible in size (200–250 μm for LUHMES and 300–350 μm for BrainSpheres) and cellular composition from batch to batch and experiment to experiment. Due to their small size they do not develop a necrotic core as many bigger in size organotypic models do [54, 56, 58–60]. That makes these two models very suitable to use for neurotoxicological studies.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have established a 3D model consisting of aggregating cultures of iPSC-derived neural cells (BrainSpheroids) based on our previous experience with 3D rat primary aggregating brain cell cultures (van Vliet et al, 2007; van Vliet et al, 2008). As part of larger efforts to create the Human-on-a-Chip, we have reported the development of a 3D brain human iPSC derived model (BrainSpheres) and its biological and medical applications (Hogberg et al, 2013; Pamies et al, 2017; Zander et al, 2017). BrainSpheres, developed in our laboratory (Pamies et al, 2017), were the first highly standardized model with hundreds of identical spheroids per batch and high reproducibility between batches and donors, thus enabling multiple applications in regenerative medicine, neuronal diseases, neuro-toxicology, and developmental biology.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional hiPSC systems have been used to study stretch injury in hiPSC-derived neuronal cultures. The benefit of this technique is that it can be performed in a 96-well plate for high throughput screening and can examine neuronal tissue of human origin (50) (54). In an intriguing approach, a recent study has shown that plating brain organoids at opposite ends of a hydrogel column leads to the development of three-dimensional axons tracts (55), which could enable investigation of diffuse axonal injury in a more biologically relevant arrangement.…”
Section: | Human Induced Pluripotent Stem Cell Systemsmentioning
confidence: 99%
“…The only non-invasive human neuronal investigations involve the use of human induced pluripotent stem cells (hiPSCs) (D). Human somatic cells (e.g., from skin fibroblasts) can be reprogrammed to induce pluripotency and these hiPSCs can then be differentiated into neurons and glia and grown into three-dimensional functional organoids, which can be used to investigate neuronal trauma, e.g., hypoxia (53) or blast (54). Cell lines may also be used for cell…”
Section: | Conclusionmentioning
confidence: 99%